Self-monetization as a double bind: the governance of affective labor of brazilian streamers - Thuns Biazzi, Amanda; Viana Braz, Matheus (AoIR Selected Papers of Internet Research, 2026)
Live streaming is an activity performed by users on media platforms, characterized by the real-time broadcasting of content with simultaneous audience interaction. Twitch (owned by Amazon), the pioneer and largest live streaming platform, markets itself as a space that fosters “belonging by enabling streamers to build community” (Twitch, 2025). While framed as a leisure activity that encourages socialization, live streaming demands significant labor: streamers must plan and organize their work, maintaining constant dedication, investing their subjectivity as well as their capitals. As a result, categories such as socialization and monetization, pleasure and labor, user and worker blur and intertwine. Considering these contradictions, this research aimed to examine how the governance of live streaming platforms shapes the subjective experiences and sociability of Brazilian streamers, particularly in relation to the monetization of leisure and social bonds. Drawing on a digital ethnography on a live streaming platform and labor life stories interviews with brazilian streamers, we argue that Twitch mobilizes a double bind of self-monetization: it promises personal and financial fulfillment while instrumentalizing meaning, affects, and self-commodification under the guise of community-driven participation.